(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Since industrial and microchannel fluid flow applications are intimately tied to the energy sector, forced convection heat transfer is one of the most often employed heat exchange methods in many thermal devices. The porous media (P.M) help to provide a vast surface area that may be utilized in a variety of applications, so its play a significant role in improving convective heat transmission inside channels containing fluid flow. On the other hand, fluids with nanoparticles could greatly increase heat conductivity. Thus, the thermal performance of forced convection systems within channels can be greatly enhanced by the combination of porous materials with nanofluids. Studies on convective heat transmission through nanofluids are covered in this article, with particular attention to the defiance associated with the use of Porous media. The coefficient of heat transmission can be improved by adding a porous medium to the channels, according to some study, while other studies have found that nanofluids overpass a higher volumes traditional fluids. Additionally, a number of studies have looked at how the flow region's geometry within forced convection channels affects heat transfer efficiency.